Photoluminescence in Er-doped 0.4Na1/2Bi1/2TiO3-(0.6-x)SrTiO3-xPbTiO3 solid solutions. (25th October 2020) - Dunce, Marija; Birks, Eriks; Antonova, Maija; Ignatans, Reinis; Nitiss, Edgars; Kundzinsh, Maris; Grube, Jurgis; Sarakovskis, Anatolijs; Sternberg, Andris
Abstract: Photoluminescence and optical second harmonic generation in Er-doped 0.4Na0.5 Bi0.5 TiO3 -(0.6- x )SrTiO3 - x PbTiO3 solid solutions is studied. Earlier, it was shown that upon increasing of PbTiO3 concentration transfer from relaxor to ferroelectric state takes place in these compositions. Here, role of PbTiO3 and Er concentration on stability of the ferroelectric state is evaluated, taking into account that luminescence, contrary to X-ray diffraction patterns and second harmonic intensity, is sensitive just to local environment around Er 3+ ions. Luminescence spectra at low temperatures are measured in order to detect variations of local environment in comparison with Er-doped Na0.5 Bi0.5 TiO3 .